(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
The optimization of pump units and their control systems, as well as increasing energy efficiency through the implementation of digital and automated control methods. The research investigates mathematical modeling of electromechanical systems, organizing effective control using frequency converters, and ways to reduce energy consumption. The dissertation proposes innovative approaches aimed at achieving high efficiency, improving reliability, and significantly reducing electricity consumption in water lifting processes.